2021
DOI: 10.1007/s10072-021-05589-1
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms in patients with epilepsy and clinically associated features in a single tertiary center

Abstract: Although depressive symptoms are the most common psychiatric comorbidity in epilepsy, they remain underestimated and untreated in a large proportion of patients. The purpose of this study was to evaluate depression severity and related clinical features in people with epilepsy using a well-reliable self-report index of mood, the Beck Depression Inventory-II (BDI-II). One-hundred seventeen adult patients with epilepsy were recruited from a tertiary epilepsy center and completed the BDI-II. A single-item analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Comorbid major depressive disorder is commonly observed in PWE, and a number of PWE have been treated with antidepressant drugs that enhance the action of 5-HT. 190 These findings led to the evaluation of clinical evidence regarding the effects of modifying 5-HT action on postictal depression in PWE. The retrospective clinical study of Bateman et al 191 showed that the degree of postictal respiratory depression in PWE who were taking SSRIs was significantly less than that in PWE who were not taking these drugs.…”
Section: Serotonin In Epilepsymentioning
confidence: 99%
See 1 more Smart Citation
“…Comorbid major depressive disorder is commonly observed in PWE, and a number of PWE have been treated with antidepressant drugs that enhance the action of 5-HT. 190 These findings led to the evaluation of clinical evidence regarding the effects of modifying 5-HT action on postictal depression in PWE. The retrospective clinical study of Bateman et al 191 showed that the degree of postictal respiratory depression in PWE who were taking SSRIs was significantly less than that in PWE who were not taking these drugs.…”
Section: Serotonin In Epilepsymentioning
confidence: 99%
“…As noted above, postictal respiratory depression is a common event in PWE, and death was precipitated by respiratory failure in most witnessed cases of human SUDEP. Comorbid major depressive disorder is commonly observed in PWE, and a number of PWE have been treated with antidepressant drugs that enhance the action of 5‐HT 190 . These findings led to the evaluation of clinical evidence regarding the effects of modifying 5‐HT action on postictal depression in PWE.…”
Section: Serotonin Hypothesis Of Sudepmentioning
confidence: 99%
“…Common symptoms included sleeping patterns, tiredness, and energy loss. Factors such as being female, having epilepsy for less than 10 years, being treated with psychotropic drugs, and reporting generalized seizures were associated with greater depression severity [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…A longer duration of epilepsy might reflect a greater period available to face stressful difficulties posed by the disease. 38 Moreover, PWE with uncontrolled seizures exhibited a higher risk of depression. Frequent seizures negatively affected seizure worry, emotional well-being, and social function.…”
Section: Discussionmentioning
confidence: 99%